Defining Molecular Treatment Targets for Bladder Pain Syndrome/Interstitial Cystitis: Uncovering Adhesion Molecules - Inal-Gultekin, Guldal; Gormez, Zeliha; Mangir, Naside (Frontiers in Pharmacology, 2022)
Bladder pain syndrome/ interstitial cystitis (BPS/IC) is a debilitating pain syndrome of unknown aetiology that predominantly affects females. Clinically BPS/ IC presents in a wide spectrum where all patients report a severe bladder pain together with one or more urinary tract symptoms. On bladder examination some have normal appearing bladders on cystoscopy whereas others may have severely inflamed bladder wall with easily bleeding areas (glomerulations) and ulcerations (Hunner’s lesion). As such, the reported prevalence of BPS/IC is also highly variable between 0.06% to 30%. Nevertheless, it is rightly defined as a rare disease (ORPHA:37202). The aetiopathogenesis of BPS/ IC remains largely unknown. Current treatment is mainly symptomatic and palliative which certainly adds to the suffering of patients with this condition. BPS/ IC is known to have a genetic component however the genes responsible are not defined yet. In addition to traditional genetic approaches, novel research methodologies involving bioinformatics are evaluated to elucidate the genetic basis of BPS/ IC. The aim of this article is to review the current evidence on the genetic basis of BPS/ IC with a view to determine the most promising targets for possible novel treatments.